Manfaat Belajar Kelompok dalam Meningkatkan Prestasi Belajar Siswa - Mishbahush Shudur (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2019)
In learning we must choose the right method, because by using the right method a person will be able to use all available time well, effectively and efficiently, so that every effort that leads to the achievement of the desired goals can be carried out properly. The learning methods that are intended and will be reviewed in this paper are learning in a group way So this paper aims to describe the benefits of group learning in improving student learning achievement that is reviewed through several literatures related to the subject, using qualitative descriptive analysis. Therefore group learning has great benefits in improving student learning achievement, so that if this has been well planned and implemented correctly, then students will be easier to achieve good and satisfying achievement.